Dynamics of transformation: Insights from an exploratory review of rice farming in the Kpong irrigation project - Takeshima, Hiroyuki; Jimah, Kipo; Kolavalli, Shashidhara; Diao, Xinshen; Funk, Rebecca Lee (International Food Policy Research Institute, 2013)
Agriculture in African South of the Sahara (SSA) can be transformed if the right public support is provided at the initial stage, and it can sustain itself once the enabling environment is put in place. Successes are also specific to the location of projects. In Ghana, interesting insights are obtained from the successful Kpong Irrigation Project (KIP), contrasted with other major irrigation projects in the country. Through an exploratory review, we describe how a productive system evolved in KIP and how public support for critical aspects (accumulation of crop husbandry knowledge, selection and supply of profitable varieties, and mechanization of land preparation) might have created a productive environment that the private sector could enter and fill in the market for credit, processing, mechanization of harvesting, and other institutional voids that typically have constrained agricultural transformation in the rest of SSA.